Penerapan Visual Efek 2D Dalam Produksi Film Animasi 3D “Neos Desert Ambush” - Muhammad Rofi’ Nur Assidiqi Haryanto; Charles De Haan (Lembaga Pengembangan Kinerja Dosen, 2022)
The main thing that distinguishes between 2D and 3D animation lies in the quality of the resulting display, namely the appearance of 2D animation that seems flat and the appearance of 3D animation that seems more volume. This study aims to manually apply 2D visual effects as an alternative in making an animated visual effect. The process of uniting a 3D animation combined with 2D animation visual effects that are created manually frame by frame and using Clip Paint Studio and Blender software. The results of this study indicate that the application of 2D animation visual effects in 3D animation is able to display a visual style that resembles 2D animation and does not require computer engine performance that is too heavy, rather than using 3D simulation methods or 3D procedural which requires strong computer resources. It is good to use in making a 3D animation with a visual style of 2D animation.